If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) = 5x + -17 Reorder the terms: 3(-3 + x) = 5x + -17 (-3 * 3 + x * 3) = 5x + -17 (-9 + 3x) = 5x + -17 Reorder the terms: -9 + 3x = -17 + 5x Solving -9 + 3x = -17 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -9 + 3x + -5x = -17 + 5x + -5x Combine like terms: 3x + -5x = -2x -9 + -2x = -17 + 5x + -5x Combine like terms: 5x + -5x = 0 -9 + -2x = -17 + 0 -9 + -2x = -17 Add '9' to each side of the equation. -9 + 9 + -2x = -17 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = -17 + 9 -2x = -17 + 9 Combine like terms: -17 + 9 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| 14x+4=15x-2 | | (7x+7)+(-4x+9)= | | 99-4x=2x+21 | | 3t+14=-2t-16 | | 3x+3=72 | | 6z-2=5z+6 | | 2x+45=x+30 | | 3(x+5)-3(-8x-7)=-45 | | 9x+7=7x-17 | | (2n-5)=4n-1 | | 6x+7y=14 | | 7y+10=9y-10 | | 12x+(-5)=-41 | | 3(x+2)-2(x-1)=8 | | 13z+1=14z-6 | | a-9=20 | | -7-(-17)= | | 5(x-3)=9x-17 | | 8z-5=7z+1 | | b^2+8b-35=0 | | x+7=6x+3 | | -2(y-3)=2y-6 | | -9(9-5y)= | | (x+2)=5 | | 4x^2-8x-21=0 | | 7=-(5-m)+4(6-m) | | 3(x-3)=3x | | 256-6x=39x+16 | | 8-7x=173-42x | | -166-10x=10x+24 | | 14.9p=74.5 | | 0.35*(1059.25+x)=x |